A case of ichthyosis hystrix: Unusual manifestation of this rare disease - Projna Biswas; Abhishek De; Sampreeti Sendur; Falguni Nag; Archana Saha; Gobinda Chatterjee (Wolters Kluwer Medknow Publications, 2014)
Ichthyosis hystrix is a term used to describe an ichthyosiform dermatosis which is characterized by hyperkeratotic spiny scales mainly over extensor aspects of limbs with palmoplantar keratoderma and occasionally associated with deafness and neurological deficit. It is a rare autosomal dominant form of ichthyosis and very few cases are reported in literature. We are presenting a 46 years-old-male patient of ichthyosis hystrix with unusual presentation. He had lesions mainly over the face and scalp with palmoplantar keratoderma and significant nail changes.